2021
DOI: 10.1039/d0na00939c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of two-dimensional phenylethylamine tin–lead halide perovskites with bandgap bending behavior

Abstract: Recently, two-dimensional (2D) metal halide perovskite materials with wide applications in perovskite-based solar cells have attracted significant attention. Among them, the 2D mixed lead-tin perovskites have not been systematically explored....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…34 Furthermore, combined experimental and theoretical work on tin–lead cocation perovskite structures demonstrates a mismatch in the energy levels, which results in the bending of the electronic bandgap by changing the Sn content. 35…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…34 Furthermore, combined experimental and theoretical work on tin–lead cocation perovskite structures demonstrates a mismatch in the energy levels, which results in the bending of the electronic bandgap by changing the Sn content. 35…”
Section: Introductionmentioning
confidence: 99%
“…34 Furthermore, combined experimental and theoretical work on tin-lead cocation perovskite structures demonstrates a mismatch in the energy levels, which results in the bending of the electronic bandgap by changing the Sn content. 35 Recently, Wei et al reported that the surface-defect passivation in a MAPbI 3 perovskite structure by 5-ammonium valeric acid (AVA) iodide leads to a reduction of the charge carrier recombination, which further gives rise to an enhancement of the stability along with 20.05% PCE. 36 Moreover, Ashari-Astani et al showed that the AVA-based 2DRP phase of perovskite exhibits additional interactions between the carbonyl heads group of the same AVA molecules, which results in the enhancement of the thermal stability of 2D perovskites.…”
Section: Introductionmentioning
confidence: 99%
“…Lead halide perovskite materials have been extensively studied in light-emitting diodes (LEDs) due to their high photoluminescence quantum yields (PLQYs) with tunable wavelengths and gradually improved stability. [1][2][3][4][5][6][7][8][9][10] Compared to all-inorganic lead halides, organic-inorganic hybrid lead halides exhibit tunable optical and physical properties because of the flexible structure and size of their organic molecules. [11][12][13][14][15] Several recent studies have demonstrated that MAPbX 3 and FAPbX 3 have high PLQYs, and narrow full width at half maxima (FWHMs).…”
Section: Introductionmentioning
confidence: 99%
“…It is discovered that this 2D perovskite exhibits asymmetric PL spectra and a lowenergy bright tail as a result of numerous exciton states, exciton−phonon interactions, and well-state radiation recombination caused by quantum and dielectric confinement effects. 45,46 Excitation−emission mapping of the (PEA) 2 PbBr 4 SC shows that the emission peak is located at 438 nm (Figure 3c), demonstrating a larger Stokes shift of 45 nm (Figure S3b) in comparison with the absorption peak located at 393 nm. Time-resolved photoluminescence (TRPL) was measured to study the carrier-recombination dynamics properties.…”
mentioning
confidence: 99%